Acylcarnitine enrichment as a characteristic of rheumatoid arthritis fibroblast-like synoviocyte metabolic fingerprint - Georgios K. Vasileiadis; Yuan Zhang; Marion Laudette; Tahzeeb Fatima; Anna-Karin Hultgård Ekwall; Reshmi Sureshkumar; Ronald van Vollenhoven; Jon Lampa; Bjorn Gudbjornsson; Espen A. Haavardsholm; Dan Nordström; Gerdur Gröndal; et al. (Journal of Translational Autoimmunity)
Objective: In rheumatoid arthritis (RA), fibroblast-like synoviocytes (FLS) alter their metabolism to support their activation. We aimed to analyse the full spectrum of metabolic alterations associated with RA by performing untargeted metabolomics in RA FLS vs. non-inflamed (NI) FLS. Methods: Untargeted annotated metabolomics was performed using mass spectrometry on ten primary RA and seven NI FLS culture extracts and 220 serum samples from participants with early RA from the randomised controlled NORD-STAR trial. Carnitine-related proteins were measured with Western blot. FLS bioenergetic profile was assessed with a Seahorse flux analyser. Results: Metabolomics analysis based on 138 annotated metabolites revealed a distinct metabolic fingerprint between RA and NI FLS. Of the 12 metabolites enriched in RA FLS, 11 were acylcarnitines. Pro-inflammatory stimulation of NI FLS also led to acylcarnitine accumulation. RA FLS exhibited lower levels of CD36, a fatty acid transporter, but similar levels of L-carnitine transporter, and carnitine palmitoyltransferase 1 A and 2 compared to NI FLS. Seahorse analyses showed no difference in fatty acid oxidation between RA and NI FLS; however, RA FLS displayed mitochondrial dysfunction and energetic impairment. Serum acylcarnitine content decreased after 24 weeks of treatment with methotrexate combined with abatacept or tocilizumab in patients with early RA achieving remission. Conclusion: Acylcarnitine accumulation is a characteristic of RA FLS metabolic fingerprint and could be linked to mitochondrial dysfunction. In patients with early RA, acylcarnitine content in serum decreases after successful anti-rheumatic treatment. These results indicate a dysregulation in acylcarnitine metabolism in RA at the joint level and systemically.